Penyuluhan Hukum Masalah Agraria atau Pertanahan di Kelurahan Sompe Kabupaten Wajo - Sulaeman; Ismail Ali; Rusdi Kadir; Indra Purnama Ramadhan; Dwi Cahyani (Compile Journal of Society Service, 2024)
The issue of disputed land, in which the question of ownership is contested, is a significant challenge in Indonesia. This is also frequently the case in Sompe Village, Wajo Regency, regardless of whether the matter has been settled through arbitration, mediation, or court proceedings. Nevertheless, numerous instances of ongoing disputes persist within the community. Such issues may be caused by a number of factors, including a lack of clarity surrounding the certification process, deficiencies in administrative procedures, inconsistencies in land boundaries, the dissemination of misinformation or incomplete data, regional expansion, a disproportionate demand for land relative to its availability, and conflicts of interest. In response to this situation, the local government of Wajo Regency has initiated the Boundary Marking Movement (Gemapatas), a programme of the Ministry of Agrarian Affairs and Spatial Planning of the Indonesian National Land Agency. This initiative aims to reinforce the legal basis for land ownership. In order to assist the government in reducing the number of disputes within the community, it is necessary to provide legal counsel on agrarian issues. This will increase understanding and provide the community with a greater understanding of land law, particularly in Sompe Village.